"Now Deborah, a prophetess, a fiery woman...": A gendered reading of Judges 4:4 - Cezula, Ntozakhe Simon (Stellenbosch Theological Journal, 2022)
This article is inspired by an article published by Reverend Bongani Finca of the Uniting Presbyterian Church in Southern Africa (UPCSA) in 1994. Rev. Finca's article is an adaptation of an address he gave on gender inequality at a Decade conference in East London, South Africa. Specifically, this article is challenged by his remark that he knows a number of men who struggle with the gender exclusivity in the language of the Church, especially in the reading of the liturgy. He then continues to say; "how many of us are working seriously at finding alternatives and revising the liturgy itself to be more gender sensitive". It is this remark that prompts this article to swing into action. For that reason, this article responds to Rev. Finca's challenge from the biblical point of view. This article thus intends to read Judges 4:4 alternatively. It intends to dispute the designation of Deborah as the wife of Lappidoth, arguing that it legitimises patriarchy.